2020
DOI: 10.3390/ijms21145038
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Prion-Inducing Properties of the G-Protein Gamma Subunit Ste18 are Regulated by Membrane Association

Abstract: Yeast prions and mnemons are respectively transmissible and non-transmissible self-perpetuating protein assemblies, frequently based on cross-β ordered detergent-resistant aggregates (amyloids). Prions cause devastating diseases in mammals and control heritable traits in yeast. It was shown that the de novo formation of the prion form [PSI+] of yeast release factor Sup35 is facilitated by aggregates of other proteins. Here we explore the mechanism of the promotion of [PSI+] formation by Ste18, an evolutionaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 102 publications
1
6
1
Order By: Relevance
“…In the WT strain, Lsb2 promoted [PSI + ] induction after both simultaneous and sequential overexpression, while Ste18 cross-seeded [PSI + ] only in the simultaneous and not the sequential protocol (Figure 6A). This result agreed with our previous data [13] and was expected as aggregates of Ste18 are entirely non-heritable in the WT strain in contrast to aggregates of Lsb2 which are heritable. However, we found that overexpressed Ste18 is able to promote [PSI + ] formation both after simultaneous and after sequential overproduction in the ssb1/2 background (Figure 6A).…”
Section: Effects Of Ssb On Ste18 Aggregationsupporting
confidence: 93%
See 3 more Smart Citations
“…In the WT strain, Lsb2 promoted [PSI + ] induction after both simultaneous and sequential overexpression, while Ste18 cross-seeded [PSI + ] only in the simultaneous and not the sequential protocol (Figure 6A). This result agreed with our previous data [13] and was expected as aggregates of Ste18 are entirely non-heritable in the WT strain in contrast to aggregates of Lsb2 which are heritable. However, we found that overexpressed Ste18 is able to promote [PSI + ] formation both after simultaneous and after sequential overproduction in the ssb1/2 background (Figure 6A).…”
Section: Effects Of Ssb On Ste18 Aggregationsupporting
confidence: 93%
“…Another yeast protein, a Gγ-subunit (Ste18), forms non-heritable detergent-resistant aggregates upon overproduction in the WT strain [13]. These aggregates resemble "mnemons" previously described for another yeast protein in the pheromone signaling pathway, Whi3 [12].…”
Section: Role Of Ssb In Cellular Memorymentioning
confidence: 53%
See 2 more Smart Citations
“…S3 ). We also could not find evidence that these mutations resulted in abnormal aggregation of Ste18, as has been recently reported under conditions of extraordinarily high cell density ( 42 ). Surprisingly, comparative analysis of predicted mRNA secondary structure does suggest the potential for unique structures to form for M2–M4 that are adjacent to the translation start site, which we speculate could disrupt translation initiation of these mRNAs ( Fig.…”
Section: Resultscontrasting
confidence: 71%